Students’ Academic Procrastination in Doing Thesis - Erfan Ramadhani; Ramtia Darma Putri (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
Academic procrastination is a delay in doing something, especially in working out demands as a student, both in working on college assignments and in doing the thesis. This study aims to reveal the level of academic procrastination of the teacher and faculty of education students of the PGRI University of Palembang, who are above the eighth semester. Students above the eighth semester are indicated to experience academic procrastination, as seen from the length of the study period. Furthermore, this study also aims to uncover the different levels of academic procrastination of male and female students in doing the thesis. This research is a comparative descriptive study which will later examine differences in the level of academic procrastination of male and female gender students using the t-test formula. This research was conducted in the faculty of education and education at the University of PGRI Palembang for three months. This research instrument uses a Likert scale model with five alternative answers. The data obtained were analyzed using t-test technique. Based on the results of the study showed that 11 study programs of the academic procrastination level of the students of the teaching and education faculty of the University of PGRI Palembang were in the high category with details of 10 courses in the high category and 1 study program in the medium category. Furthermore, the results of the hypothesis test showed that the level of academic procrastination of the students of the faculty of education and education at the PGRI University of Palembang, male and female, there were no significant differences. The results of this study can be used as a basis for providing services to students so that students no longer occur in completing studies.